Pretreatment Lignoselulosa dari Jerami Padi dengan Deep Eutectic Solvent untuk Meningkatkan Produksi Bioetanol Generasi Dua (Lignocellulose Pretreatment of Rice Straw using Deep Eutectic Solvent to Increase Second-Generation Bioethanol Production) - Nurwahdah, Nurwahdah; Naini, Al-Arofatus; Nadia, Asma; Lestari, Ratri Yuli; Sunardi, Ph.D., Sunardi (Kementerian Perindustrian, 2018)
Current issues of energy sector in Indonesia can be summarized as depletion of fossil energy reserves which is dominated by fuel oil and coal. Oil production continues to decline and the increase in oil fuels demand lead to increase imports of crude oil and oil fuels. To use lignocellulosic biomass waste has become a major alternative to replace fossil fuels and chemical feedstocks production. In 2015, total rice production in South Kalimantan reached 2,140,276 ton and rice straws were abundant waste which could be utilized as raw material for bioethanol production. Pretreatment process of lignocellulose is a crucial step to remove lignin because of the complex chemical cross-linking between chemical components. Delignification of lignin can increase the accessibility and digestibility of enzymatic, and help to promote enzymatic hydrolysis. Nowadays, pretreatment process with green chemistry method is continuesly developed by researcher to reduce the production costs and thus avoid adverse effects on human and the environment. This article disscussed about green methods for pretreatment of lignocellulosic material using deep eutectic solvent (DES) to increase second-generation bioethanol production in South Kalimantan.